Tourism and Australian Beach Cultures Revealing Bodies - Metusela, Christine; Waitt, Gordon (Tourism and Cultural Change, 2012)
This book explores the ever-changing interconnections between bodies, subjectivities, space, beach cultures and tourism, engaging with the geographies of the beach: its makings, boundaries and meanings for the West. Drawing on feminist scholarship, Christine Metusela and Gordon Waitt explore the reciprocal relationship between bodies and beaches, focusing on the shifting intersection between age, race, class, sex, gender and national discourses that naturalise particular bodies as belonging on the beach. The authors critically examine how subjectivities of bodies are produced under specific circumstances - the Illawarra beaches from 1830-1940, some 80 kilometres beyond the metropolitan centre of Sydney. Drawing on modernisation and nation building discourses, the paradoxical qualities of the Illawarra are highlighted; imagined as both the New Brighton of Australia and the Sheffield of the South